2020
DOI: 10.1152/ajplung.00286.2020
|View full text |Cite
|
Sign up to set email alerts
|

Role of the renin-angiotensin system in the development of severe COVID-19 in hypertensive patients

Abstract: A new form of severe acute respiratory syndrome (SARS) caused by SARS-CoV-2, called COVID-19, has become a global threat in 2020. The mortality rate from COVID-19 is high in hypertensive patients, making this association especially dangerous. There appears to be a consensus, despite the lack of experimental data, that angiotensin II (Ang II) is linked to the pathogenesis of COVID-19. This process may occur due to acquired deficiency of angiotensin-converting enzyme 2 (ACE2), resulting in reduced degradation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…We found that COVID-19 symptomatic (2.45%) patients were more experienced with new-onset hypertension than asymptomatic (1.41%) patients. Downregulation of ACE-2 enzymes results in the reduced degradation of angiotensin II (ANG II) (Mascolo et al, 2020;Silva-Aguiar et al, 2020). Furthermore, the imbalance of ANG II in Renin-angiotensin system (RAS) can lead to genesis and worsening of hypertension in COVID-19 patients (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We found that COVID-19 symptomatic (2.45%) patients were more experienced with new-onset hypertension than asymptomatic (1.41%) patients. Downregulation of ACE-2 enzymes results in the reduced degradation of angiotensin II (ANG II) (Mascolo et al, 2020;Silva-Aguiar et al, 2020). Furthermore, the imbalance of ANG II in Renin-angiotensin system (RAS) can lead to genesis and worsening of hypertension in COVID-19 patients (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Soria-Castro et al [105] recently reported that COVID-19 patients showed increased carboxypeptidase A3 (CPA3), which is also known for its function in converting angiotensin II to angiotensin 1-7 [81]. Another enzyme prolylcarboxypeptidase that can catalytically convert angiotensin II to angiotensin 1-7 may also be involved in COVID-19 pathophysiology [106]. Taken together, these findings suggest potential involvement of TOP or other endopeptidases and carboxypeptidases in the pathophysiology of COVID-19 infection is an area worthy of further investigation.…”
Section: Effects Of Top In Intracellular Processing Of Angiotensin 1-7 and Its Potential Involvement In Covid-19 Pathogenesismentioning
confidence: 99%
“…Hypertension’s integrative role with other organs affects RAS systemically and locally, which is activated by distinct signals from differing physiologic and pathophysiologic conditions ( 171 , 172 ). Essential hypertension can be delineated into two groups based on plasma renin activity: those with low activity, and those with normal-to-high activity ( 173 ). Studies show that hypertension with high plasma renin activity relates to increased cardiovascular complications and vascular damage ( 173 175 ).…”
Section: Primary Risk Factorsmentioning
confidence: 99%
“…Essential hypertension can be delineated into two groups based on plasma renin activity: those with low activity, and those with normal-to-high activity ( 173 ). Studies show that hypertension with high plasma renin activity relates to increased cardiovascular complications and vascular damage ( 173 175 ). The deleterious effects may destroy ACE2 mRNA and protein activity in tissue, as hypertensive clinical and experimental models show, primarily in the kidneys and heart and thus depict hypertensive progression decreasing local ACE2 activity ( 97 , 176 180 ).…”
Section: Primary Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation